2019
DOI: 10.1002/eco.2144
|View full text |Cite
|
Sign up to set email alerts
|

Thirty years after Balbina Dam: Diversity and floristic composition of the downstream floodplain forest, Central Amazon, Brazil

Abstract: The construction of hydroelectric dams causes changes in the diversity and floristic composition of floodplain forests due to the irregularity of the hydrological regime in rivers downstream from the dams. In the Amazon Basin, plans for the construction of dams are threatening the igapós, forests flooded by blackwater rivers. In these floodplains, the distribution of tree species is synchronized with periodic flood events of the topographic gradient. Previous studies on the Balbina Dam show an altered flood pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 56 publications
3
26
0
1
Order By: Relevance
“…This is in agreement with Fearnside et al (2016) [20], who found that hydroelectric projects can stimulate deforestation around reservoirs in the Amazon. Similar LULCC patterns have been found in other hydroelectric dams constructed in the Brazilian Amazon such as Balbina [41], Belo Monte [42], and Tucuruí [43].…”
Section: Discussionsupporting
confidence: 79%
“…This is in agreement with Fearnside et al (2016) [20], who found that hydroelectric projects can stimulate deforestation around reservoirs in the Amazon. Similar LULCC patterns have been found in other hydroelectric dams constructed in the Brazilian Amazon such as Balbina [41], Belo Monte [42], and Tucuruí [43].…”
Section: Discussionsupporting
confidence: 79%
“…This occurs because the flood travels through the igapó forest from the low levels to the highest topographies, corroborating the concept of lateral connectivity proposed by Ward (1989). However, in the Uatumã area, lateral connectivity was altered along the entire topography (Rocha et al 2019). The suppression of flooding in the high quotas of the Uatumã area acted as a limiting factor for the establishment, for example, of A. jauari.…”
Section: Effect Of the Flood Gradient And Genera Distributionsupporting
confidence: 75%
“…A critical need to reformulate EIAs for the licensing of hydroelectric dams was also pointed out in a recent study in which the authors observed the multiple effects after the installation of the Balbina hydroelectric dam in central Amazon. The operation of this hydroelectric plant drastically changed the natural flooding pulses of the Uatumã River downstream of the dam [ 51 ]. Flooded area by Balbina was predicted by Eletronorte to be 1654 km 2 , while posterior analyzes detected 2996 km 2 [ 29 , 52 ].…”
Section: Discussionmentioning
confidence: 99%